Preseption of Students About the Use of Goski Application (Google Sites Kondisi Geologis Indonesia) as an IPS Learning Media - Mia Andria Ningsih; Yusuf Hanafi; Joko Yuniarto (STKIP Taman Siswa Bima, 2024)
The application of learning media in the learning process is very important. Teachers are required to create an interesting and interactive learning atmosphere, one of which is by using technology-based learning media. One learning media that can be used is the GOSKI application (Google Sites Geological Conditions of Indonesia). The aim of this research is to determine students' responses to the implementation of the GOSKI application in social studies learning at SMPN 10 Malang. Data collection was carried out through observation, interviews and distributing questionnaires. The method used in this research is descriptive quantitative. Based on the results of the questionnaire analysis that was distributed to students, a percentage of 86% was obtained, which shows a positive response from students towards the application of GOSKI learning media. This shows that the GOSKI application is suitable for use in the learning process. A follow-up recommendation from this research is to examine the application of GOSKI learning media combined with game-based learning.